2017
DOI: 10.1039/c7nj02019h
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization, computational and antimicrobial activities of a novel iridium thiourea complex

Abstract: A novel octahedral iridium(iii)thiourea complex with potential medical applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…All kinds of intracellular mechanisms of action are involved in the activity of these compounds, for example, the inhibition of cellular iron uptake through transferrin, the upregulation of the metastasis suppressor protein, and the improvement of reactive oxygen species catalyzed by the formation of metal complexes . Additionally, recent reports confirmed that the biological activity of TSC ligands could be modified and improved after being coordinated with transition metal ions . The versatility of TSC ligands coordinated with metal ions (Fe­(II), Co­(II), Ru­(III), Rh­(II), Ru­(II), etc.)…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…All kinds of intracellular mechanisms of action are involved in the activity of these compounds, for example, the inhibition of cellular iron uptake through transferrin, the upregulation of the metastasis suppressor protein, and the improvement of reactive oxygen species catalyzed by the formation of metal complexes . Additionally, recent reports confirmed that the biological activity of TSC ligands could be modified and improved after being coordinated with transition metal ions . The versatility of TSC ligands coordinated with metal ions (Fe­(II), Co­(II), Ru­(III), Rh­(II), Ru­(II), etc.)…”
Section: Introductionmentioning
confidence: 99%
“…21 Additionally, recent reports confirmed that the biological activity of TSC ligands could be modified and improved after being coordinated with transition metal ions. 22 The versatility of TSC ligands coordinated with metal ions (Fe(II), Co(II), Ru(III), Rh(II), Ru(II), etc.) with the aid of sulfur atom or nitrogen atom to act as a monodentate ligand or via these two atoms as a bidentate ligand have precipitated some renewed research in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…Half-sandwich Os(II), Ir(III), and Ru(II) TSC complexes have shown promising anticancer potential in vitro and in vivo, respectively. [32][33][34] Considering that ferrocene and the half-sandwich Ir III complexes have shown favorable potential in anticancer, several ferrocene-appended TSC-Schiff base pro-ligands were created in this study and then coordinated with the basic iridium precursors to produce eight half-sandwich Ir III Fc-TSC-Schiff base complexes (IrFc1-IrFc8, Chart 1). The preliminary MTT (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide) assay was used to assess the in vitro anti-proliferation potential of these complexes.…”
Section: Introductionmentioning
confidence: 99%